Therapeutic potential of palm oil vitamin E-derived tocotrienols in inflammation and chronic diseases: Evidence from preclinical and clinical studies - Zainal, Zaida; Khaza'ai, Huzwah; Radhakrishnan, Ammu Kutty; Chang, Sui Kiat (Elsevier, 2022)
Palm oil is rich in tocotrienols (T3s), a type of vitamin E that has garnered considerable research interest as it exhibits anti-inflammatory as well as antioxidant characteristics that are comparable to or exceed those of tocopherols (Toc). Notably, T3 must be consumed as it cannot be produced by the human body. Here, we reviewed the anti-inflammatory activities of T3s in the prevention and treatment of various inflammatory disorders; focusing on recent preclinical and clinical studies. There is compelling data from experimental models and human studies that shows that T3 administration can inhibit the release of various inflammatory mediators that contribute to age-related disease by enhancing oxidative stress, reducing melanin production and skin damage, and preventing cardiovascular disease and stroke. There is evidence to show that T3s possess neuroprotective, anticancer, and anti-osteoporosis properties. In addition, T3s also protect the gastrointestinal tract, facilitate blood glucose control in people with diabetes, and prevent fatty liver disease. Furthermore, results from some clinical studies suggest that T3s are beneficial nutritional supplements with no evident side-effects when administered to patients with neurological or cardiovascular disorders. There is growing evidence from clinical trials that shows that T3s can help prevent dementia and Alzheimer's disease. More well-designed clinical trials, as well as human intervention studies, are required to confirm the health benefits of palm T3.